Metal About the Hip and Artifact Reduction Techniques: From Basic Concepts to Advanced Imaging - Khodarahmi, Iman; Isaac, Amanda; Fishman, Elliot K.; Dalili, Danoob; Fritz, Jan (Seminars in Musculoskeletal Radiology, 2019)
Promising outcomes of hip replacement interventions in this era of aging populations have led to higher demands for hip arthroplasty procedures. These require effective methods and techniques for the detection of postoperative outcomes and complications. Based on the presence or absence of radiographic findings, magnetic resonance imaging (MRI) and computed tomography (CT) may be required to detect and further characterize different causes of failing implants. Yet metal-related artifacts degrade image quality and pose significant challenges for adequate image quality. To mitigate such artifacts in MRI, a set of techniques, collectively known as metal artifact reduction sequence (MARS) MRI, were developed that optimize the framework of the conventional pulse sequences and exploit novel multispectral and multispatial imaging methods such as Slice Encoding for Metal Artifact Correction (SEMAC) and Multi-Acquisition Variable-Resonance Image Combination (MAVRIC). Metal-induced artifacts on CT can be effectively reduced with virtual monochromatic reconstruction of dual-energy CT data sets, metal artifact reduction reconstruction algorithms, and postprocessing image visualization techniques.
Keywords: MRI; CT; implant; hip arthroplasty; dual energy; metal artifact reduction